ASSESSMENT OF BURNOUT OF NURSES AND ITS IMPACT ON RESILIENCE IN MAJOR HOSPITAL DEPARTMENTS - NAWAZ, N; AHMAD, F; MUMTAZ, A (Biological and Clinical Sciences Research Journal, 2024)
Burnout among nurses is a critical issue that can significantly affect their professional performance and overall well-being. Personal resilience has been suggested as a potential mitigating factor for burnout symptoms. Understanding the relationship between burnout and resilience can inform interventions to support nurses in high-stress environments. Objective: To assess the burnout levels of nurses working in central hospital departments and their association with personal resilience. Methods: A cross-sectional study was conducted in the Nursing Department of a tertiary care hospital from April 2023 to April 2024. A total of 200 registered and licensed nurses from major departments who were directly involved in patient care were selected through convenience sampling. Data were collected using an anonymous questionnaire written in both English and Urdu. The survey comprised three sections: demographic details, the Maslach Burnout Inventory General Survey, and the Connor-Davidson Resilience Scale. Statistical analysis was performed using SPSS version 25. Descriptive statistics were used to summarize the data, and Pearson correlation analysis was conducted to assess the association between burnout and resilience variables. Results: The mean scores of burnout variables were 2.50 ± 1.30 for emotional exhaustion, 2.18 ± 1.18 for cynicism, and 2.21 ± 1.08 for reduced professional performance. The mean scores for resilience variables were 33.08 ± 7.15 for tenacity, 22.68 ± 5.63 for strength, and 10.82 ± 2.36 for optimism. A significant negative association was found between resilience levels and burnout symptoms; higher resilience scores were associated with lower burnout symptoms, though these associations were not statistically significant. Conclusion: The study identified high burnout and moderate resilience levels among nurses. Burnout and resilience were negatively associated, suggesting that enhancing resilience may play a role in mitigating burnout among nurses. Interventions aimed at building resilience could be beneficial in reducing burnout and improving professional performance.